The Issue of Race in Post-Colonial African American Poetry - Ameer Haraj, Sahar Abdul (Opción, 2019)
With studying of selected poems by Gwendolyn Brooks, the researcher aims to investigate the issue of race in Post-Colonial African American poetry via comparative- typological approaches. Brooks tries to depict the social inequality and the subordination of her people that has happened during the sixties of the twentieth century. As a result, Brooks’ poetry was an attempt to forcefully encourage the blacks to be inspired by their heritage to attain their principal role in the society. As a conclusion, Brooks places emphasis on the humanistic love too being one of the principal requirements to a happy and brotherly life.